Pengelolaan Infrastruktur Air Bersih Berkelanjutan Berbasis Masyarakat (Studi Kasus: Modal Sosial dalam Pengelolaan Sumber Air di Hutan Bambu Desa Sumbermujur, Lumajang) - Rindang Alfiah; Ismu Rini Dwi Ari; Septiana Hariyani (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2017)
Development has a purpose to improve the standard of living. The government began to apply the concept of sustainable development through the SDG's programme which integrates economic development with the socio-cultural and environmental aspects. This study aims to identify the participation (social capital) of Sumbermujur Village community on the activities of conservation that can maintain the quality and quantity of the Sumber Deling springs. The method used is social network analysis based on three measures of rate of participation, density and centrality. The results showed that the values showed moderate and low participation rates with high density and centrality values with some actors in the network. this is quite good because it can help in the development of water management.